A Guided Inquiry into a Dubious, Pervasive, All-American Organization, the Ku Klux Klan - Bickford, John Holden; Clabough, Jeremiah (Teaching History: A Journal of Methods, 2020)
The historical roots of White nationalism in the United States appear in the history of the Ku Klux Klan (KKK). Historians have traced three distinct surges in KKK membership and activity. Recently, White nationalism has reemerged, as evidenced in the 2017 Charlottesville, Virginia events. This guided inquiry positions students explore the Klan’s dubious place in American history. Primary and secondary sources from each wave, including contemporaneous documents from recent events, are coupled with discipline-specific close-reading and text-based writing strategies.